2005
DOI: 10.1111/j.1365-2265.2005.02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive enzyme immunoassay for anti‐Müllerian hormone and the evaluation of potential clinical applications in males and females

Abstract: We have developed a sensitive and specific assay for AMH. Serum AMH in men with male factor infertility is lower than in normal men. Levels of AMH in pregnancy are higher than normal menstrual cycle levels suggesting a foeto-placental contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 37 publications
6
67
1
7
Order By: Relevance
“…Similarly, seminal AMH concentrations have been found to be significantly lower 11,[20][21][22][23] or equal 15 in subfertile men compared with fertile controls. In order to further elucidate the role of inhibin B and AMH in male subfertility we designed a prospective control-matched study with the aim of determining serum inhibin B and AMH concentrations in men with different causes of subfertility.…”
Section: The Role Of Inhibin B and Amh Basal Concentrationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, seminal AMH concentrations have been found to be significantly lower 11,[20][21][22][23] or equal 15 in subfertile men compared with fertile controls. In order to further elucidate the role of inhibin B and AMH in male subfertility we designed a prospective control-matched study with the aim of determining serum inhibin B and AMH concentrations in men with different causes of subfertility.…”
Section: The Role Of Inhibin B and Amh Basal Concentrationsmentioning
confidence: 96%
“…3,12-14 Serum AMH concentrations have been found to be significantly lower 15,16 or equal [17][18][19] in subfertile men compared with controls. Similarly, seminal AMH concentrations have been found to be significantly lower 11,[20][21][22][23] or equal 15 in subfertile men compared with fertile controls.…”
Section: The Role Of Inhibin B and Amh Basal Concentrationsmentioning
confidence: 99%
“…AMH (ng/ml) was determined in Rotterdam by an in-house developed AMH-ELISA (enzyme-linked immunosorbent assay; commercially available as the GenII Beckmann Coulter, Beckman Coulter, Inc.) (Kevenaar et al, 2006). Previously, we have shown that AMH immunoreactivity in serum is stable during storage and after repeated freeze -thaw cycles (Al-Qahtani et al, 2005;Kevenaar et al, 2006), thus neither storage nor transport should affect measured AMH concentrations. This highly sensitive ELISA uses AMH standards in the range of 5-0.037 ng/ml.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…In one study, Al-Qahtani et al demonstrated unchanged immunoreactivity after repeated freeze-thaw cycles at -80°C after short-term storage for 4 days with an in-house AMH method [13]. In another study [18], Gen II-AMH increased by 15% in serum and 5% in plasma after three cycles of freeze-thawing.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, few studies have been conducted on the impact of longterm freezer storage on AMH results [12]. The influence on AMH results after intermittent thawing-which is often required in long-term studies-has also been discussed, as analytical methods improve and change over time [13,14].…”
Section: Introductionmentioning
confidence: 99%